2021
DOI: 10.3847/1538-4357/ac324d
|View full text |Cite
|
Sign up to set email alerts
|

Weak Damping of Propagating MHD Kink Waves in the Quiescent Corona

Abstract: Propagating transverse waves are thought to be a key transporter of Poynting flux throughout the Sun’s atmosphere. Recent studies have shown that these transverse motions, interpreted as the magnetohydrodynamic kink mode, are prevalent throughout the corona. The associated energy estimates suggest the waves carry enough energy to meet the demands of coronal radiative losses in the quiescent Sun. However, it is still unclear how the waves deposit their energy into the coronal plasma. We present the results from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 109 publications
4
19
0
Order By: Relevance
“…The catalogue is used to undertake a statistical study of the propagating kink waves providing estimates for the damping rate and propagation speeds of the waves, presenting some details of how the propagating kink waves evolve. It is found that the equilibrium parameter, which quantifies the degree of wave damping, has a broad range of values, which indicates that in some of the coronal loops, the propagating kink waves are only weakly damped (this is aspect is discussed further in Morton et al 2021). The damping length of the propagating kink waves is also estimated, which is found to be broadly comparable to the previous estimates of (Hahn & Savin 2014).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The catalogue is used to undertake a statistical study of the propagating kink waves providing estimates for the damping rate and propagation speeds of the waves, presenting some details of how the propagating kink waves evolve. It is found that the equilibrium parameter, which quantifies the degree of wave damping, has a broad range of values, which indicates that in some of the coronal loops, the propagating kink waves are only weakly damped (this is aspect is discussed further in Morton et al 2021). The damping length of the propagating kink waves is also estimated, which is found to be broadly comparable to the previous estimates of (Hahn & Savin 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Hence, the propagating kink waves can be strongly damped or very weakly damped. The median value is ∼ 11, and a mean value of ∼ 18, which is greater than that found for the standing kink modes (see Morton et al 2021, for a full discussion of the importance of the observed values of the equilibrium parameter).…”
Section: Equilibrium Parametermentioning
confidence: 71%
See 2 more Smart Citations
“…Lately, Van Doorsselaere et al (2021) developed a nonlinear damping model for standing kink waves and showed that the damping time is inversely proportional to the oscillation amplitude, where they also found a notable match with the observation (Nechaeva et al, 2019). Compared to standing transverse oscillations, propagating kink waves have received little attention (Thurgood et al, 2014;Morton et al, 2021).…”
Section: Introductionmentioning
confidence: 90%